Analysis of Student’s Pronunciation Ability of Twelfth Grade Student at SMAN 8 Jambi - Manurung, Laurent Margaretta; Ismiyati, Yanti; Yurni, Yurni (JELT: Journal of English Language Teaching, 2024)
This study aimed to determine students' pronunciation skills through Google Translate microphones. This study is a quasi-experimental study involving a control class and an experimental class. The participants in this study were 30 twelfth-grade students of SMA 8 of Jambi City. The research instrument has been tested for validity and reliability by conducting pre-test and post-test. The instrument was given in the control class and experimental class before and after providing treatments. The treatments were only given to the experimental class meanwhile in control class remained using the conventional teaching technique. The result of the study showed that the experimental class had improved their Pronunciation ability. The average pre-test score of the experimental class was 45, while the average of the control class was 30.7 based on statistical analysis. The Google Translate microphone was implemented in the experimental class, and the average score increased to 70.7 while the control class was 30 students. Based on these data, the experimental class has a higher average score in the post-test while the control class gets a lower average score, the conclusion is that the use of Google Translate microphone can improve students' pronunciation ability.